Resistance Exercise Sessions Comprising Multijoint vs. Single-Joint Exercises Result in Similar Metabolic and Hormonal Responses, But Distinct Levels of Muscle Damage in Trained Men - Barbosa, Paulo Henrique (2024)
Barbosa, PH, Bueno de Camargo, JB, Jonas de Oliveira, J, Reis Barbosa, CG, Santos da Silva, A, Dos-Santos, JW, Verlengia, R, Barreira, J, Braz, TV, and Lopes, CR. Resistance exercise sessions comprising multijoint vs. single-joint exercises result in similar metabolic and hormonal responses, but distinct levels of muscle damage in trained men. J Strength Cond Res 38(5): 842-847, 2024 - Resistance-type exercise (RE) elicits distinct acute metabolic and hormonal responses, which can be modulated by the manipulation of training variables. The purpose of this study was to compare the metabolic (blood lactate and estimated lactic anaerobic system energy expenditure) and hormonal (growth hormone [GH]) responses to RE sessions composed exclusively of multijoint (MULTI) or single-joint (SINGLE) exercises. Assessments of creatine kinase (CK) levels were also performed. In a crossover design, 10 recreationally resistance-trained men (age: 26.9 ± 3.0 years, total body mass: 83.2 ± 13.8 kg; height: 176 ± 7.0 cm; training experience: 5.5 ± 2.4 years) were randomly submitted to both protocols. Blood collections were made pre, 3 minutes after, and 36 hours after each experimental session. No significant difference between MULTI vs. SINGLE was observed for the rises in blood lactate (p = 0.057) and GH (p = 0.285) levels. For CK, a significant difference between the protocols was noted, in which MULTI resulted in significant rises after 3 minutes (p = 0.017) and 36 hours (p = 0.043) compared with SINGLE. In conclusion, the findings of this study suggest that resistance-trained individuals display similar metabolic and hormonal responses when performing MULTI and SINGLE exercise protocols. Also, RE sessions comprising MULTI exercises induce a higher magnitude of muscle damage, which may require a longer recovery period compared with SINGLE.